MEMAHAMI ISLAMIC CENTER KOTA LHOKSEUMAWE MELALUI GENIUS LOCI - Aliza Azzahra; Deni; Dela Andriani (Rumoh Journal of Architecture, 2022)
The Great Mosque Islamic Center is majestically in the middle of Lhokseumawe City, built-in 2001. The Great Mosque Islamic Center is a forum for Muslim development, educational activities, Islamic activities, studies, training, and socioeconomic and routine recitation. The Islamic Center is a symbol of the existence of Muslims in Lhokseumawe City. The function of the place used can be interpreted as having a relationship between man and his god, man with the environment as a support, and the involvement of the universe in achieving the meaning of an environment. This study uses a qualitative method with an exploratory approach, by observing community activities and interactions through space identification. The purpose of the research is to understand how an ideal space and place is able to accommodate all activities visitors inside and outside. The approach used is Genius Loci, which utilizes local potential such as being responsive to the local nature, culture and other things that are unique to that place or building. The results of the study show that the Great Mosque of Islamic Center has a spirit of place, namely a special atmosphere that distinguishes it from other places in Lhokseumawe City. The activities carried out by visitors are predominantly oriented towards the visuals of the mosque, the large yard makes many activities can be accommodated properly.